Profitabilitas, Intensitas Modal Dan Penghindaran Pajak : Ukuran Perusahaan Sebagai Variabel Pemoderasi - Nur Amiah (Jurnal Literasi Akuntansi, 2022)
Purpose: This research aims to find out and analyze the effect of Profitability and Capital Intensity on Tax Avoidance moderated by Company Size. Method: The sample used in this study was a manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2015-2019 as many as 49 companies obtained by purposive sampling method. This research technique uses multiple linear analysis and absolute difference value analysis. Finding: The results of this study showed that the profitability variable (ROE) had a significant negative effect on tax avoidance, capital intensity had no effect on tax avoidance. Corporate size (SIZE) can moderate the positive influence of profitability relationship (ROE) and capital intensity (capital intensity) on tax avoidance. Novelty: The novelty of the study, researchers added variable moderation of company size and different time periods. By integrating several topics regarding tax avoidance variables that are influenced by two variables, namely profitability and capital intensity.